ANALISIS TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN YANG DIBERIKAN OLEH RUMAH SAKIT DENGAN METODE SERVQUAL, IMPORTANCE PERFORMANCE ANALYSIS DAN CUSTOMER SATISFACTION INDEX - Ega Subiyantoro; Atika Nurani Ambarwati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Given the importance of health services for every resident, making a hospitalhas an important role in responding to the community's need for healthservices. Health services should be enjoyed by all communities. The role of thehospital as a curative, rehabilitative, promotive and preventive serviceprovider, occupies an important role in the health service system, so efforts toimprove the quality of hospital services become a priority in healthdevelopment. It is feasible to strive for the whole society to enjoy health servicesin an affordable and evenly served (Azwar, 1996), in the research of patientsatisfaction on services provided by this hospital will use three methods ofcustomer satisfaction that is Method Imprtance Perfomance Analysis , ServqualMethod, Customer Method and Satisfaction Index. By using research variablesare responsiveness, reliability, assurance, empathy and physical evidence.Based on servqual analysis there are still many negative values, this indicatesthat the patient has not felt not satisfied with the services provided by thehospital or the quality of service has not been able to satisfy the patient. Basedon the Cartesian diagram of Importance Perfomance Analysis, patients feel lesssatisfied with service performance compared to service satisfaction, wherepatients consider less important service performance for patients but theimplementation is considered normal. Based on the value of customersatisfaction index service performance criteria provided by the hospital is stillnot good degan CSI value of 32.9%Keywords: Importance Performance and Analysis, Kepuasan Pelanggan, Servqual dan Customer Satisfaction Index